2013
DOI: 10.1159/000350287
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Intravenous Immunoglobulin in Chronic Inflammatory Demyelinating Polyneuropathy Evaluated by Grip Strength Measurement

Abstract: Background: Optimal dose and timing of repeated intravenous immunoglobulin therapy (IVIg) for intractable chronic inflammatory demyelinating polyneuropathy (CIDP) patients have not been determined. The aim of this study was to optimize dose and timing of IVIg for CIDP patients who need frequent IVIg using daily grip strength measurement. Methods: Repeated IVIg were administered for two intractable CIDP patients. Grip strength was recorded at home every day to access the clinical change in symptoms, and dose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…Myometry has been shown to be a potentially useful tool to monitor disease activity in CIDP, and it is now used more commonly, although with varied methods, in many units. The independent usefulness of grip myometry has been further documented in recent literature . That myometry has the potential to be valuable is unquestionable; however, inter‐ and intrarater reliability may be an issue.…”
Section: Ivig For Cidp: How Is Efficacy Monitored?mentioning
confidence: 93%
“…Myometry has been shown to be a potentially useful tool to monitor disease activity in CIDP, and it is now used more commonly, although with varied methods, in many units. The independent usefulness of grip myometry has been further documented in recent literature . That myometry has the potential to be valuable is unquestionable; however, inter‐ and intrarater reliability may be an issue.…”
Section: Ivig For Cidp: How Is Efficacy Monitored?mentioning
confidence: 93%
“…Symptomatic improvement following IVIG in CIDP, multifocal motor neuropathy (MMN), and MG is transient, and the IVIG must be administered repeatedly at intervals ≤3-4 weeks to maintain its clinical effect (Ruegg et al, 2004;Harbo et al, 2009b;Lin et al, 2011;Pollard and Armati, 2011). Recent reports of individualized regimens show that 28%-60% of CIDP patients require IVIG every 2 weeks or even more frequently for optimal maintenance of strength (Broyles et al, 2013;Kokubun et al, 2013;Kuitwaard et al, 2013;Rajabally et al, 2013). In contrast to transient relief of symptoms, true remission often requires immunomodulators other than IVIG, as shown in Fig.…”
Section: Other Actions Of Ivig That Do Not Involve Competition Per Sementioning
confidence: 99%
“…In the Kokubun et al . study, improvement was demonstrated using grip strength, which was shown by Vanhoutte et al . to be a more sensitive outcome measure than the inflammatory neuropathy cause and treatment (INCAT) disability score.…”
mentioning
confidence: 98%
“…The stated goal is to reduce the amount IVIg to the lowest effective dose so as to prevent overtreatment. However, some patients may benefit from escalation in their maintenance dose beyond that provided by standard treatment . How one determines that optimal dose is not always obvious.…”
mentioning
confidence: 99%
See 1 more Smart Citation